2017
DOI: 10.1158/1078-0432.ccr-16-2622
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitor Enhances the Efficacy of MEK Inhibitor through NOXA-Mediated MCL1 Degradation in Triple-Negative and Inflammatory Breast Cancer

Abstract: Purpose Inflammatory breast cancer (IBC), diagnosed clinically, and triple-negative breast cancer (TNBC), diagnosed by molecular receptor status, are the two most aggressive forms of breast cancer, and both lack effective targeted therapies. We previously demonstrated involvement of histone deacetylase (HDAC) inhibitor entinostat in regulating apoptosis in IBC and TNBC cells; here, we aimed to identify novel combination therapy candidates. Experimental Design Potential therapeutic targets were identified by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
2
36
1
Order By: Relevance
“…50 To definitively establish the CRBN dependence of this degradation mechanism, a CRBN knockout cell line of OPM2 CRBN-/was generated using CRISPR Cas9 gene editing and this In contrast, the same treatment of OPM2 CRBN-/cells with dMCL1-2 was ineffective ( Figure 7c). MCL1 levels experienced insignificant changes in abundance when CRBN is absent (lanes [15][16][17][18]. Consistent with our proposed mode of action, OPM2 CRBN-/cells no longer possess the capability to form the CUL4A-DDB1 complex and ubiquitinate MCL1, preventing any degradation from occurring, and supporting the UPP degradation mechanism of dMCL1-2.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…50 To definitively establish the CRBN dependence of this degradation mechanism, a CRBN knockout cell line of OPM2 CRBN-/was generated using CRISPR Cas9 gene editing and this In contrast, the same treatment of OPM2 CRBN-/cells with dMCL1-2 was ineffective ( Figure 7c). MCL1 levels experienced insignificant changes in abundance when CRBN is absent (lanes [15][16][17][18]. Consistent with our proposed mode of action, OPM2 CRBN-/cells no longer possess the capability to form the CUL4A-DDB1 complex and ubiquitinate MCL1, preventing any degradation from occurring, and supporting the UPP degradation mechanism of dMCL1-2.…”
supporting
confidence: 79%
“…carboxylic acid (15). To a solution of free amine 14 (0.208 g, 0.24 mmol) in THF (1.9 mL) and 13 5-((3aS,4S,6aR)-2-oxohexahydro-1H-thieno[3,4-d]imidazol-4yl)pentanoate (16). To a suspension of biotin (0.057 g, 0.23 mmol) in DMF (2 mL), was added Et3N (0.073 g, 0.10 mL, 0.73 mmol) under stirring at ambient temperature.…”
Section: Pyrazol-4-yl)-3-(3-(naphthalen-1-yloxy)propyl)-1-(2-(piperazmentioning
confidence: 99%
See 1 more Smart Citation
“…S8 A-C). The anti-tumor function of HDACis is mostly exerted via the induction of apoptosis, which activates the apoptosis cascade, including decreases in MCL1 (21,22) and BCL-2 (23). However, the immunoblotting analysis showed that the administration of HDACis to OVCA433 cells only slightly decreased the MCL1 expression levels (Fig.…”
Section: Dub3-mcl1 Drives Chemoresistance In Ovarian Cancer Via Inhibmentioning
confidence: 96%
“…Histone deacetylase (HDAC) enzymes remove acetyl groups from histone tails. Thus, HAT/HDAC activity balance is an important determinant of gene regulation, and it has accordingly emerged as a potential therapeutic target for the treatment of various diseases (48,62,108,127). DNA methylation regulates gene expression.…”
Section: Chromatin Reorganization and Innate Immune Memorymentioning
confidence: 99%